1991
DOI: 10.1152/ajpregu.1991.260.3.r486
|View full text |Cite
|
Sign up to set email alerts
|

Lateral distribution of hypothalamic signals controlling thermoregulatory vasomotor activity and shivering in rats

Abstract: The present study explored the laterality of central nervous thermoregulatory control in anesthetized rats by measuring paw skin vasomotor activity and cold-induced shivering in hind leg muscles during unilateral preoptic area and anterior hypothalamus (POAH) warming and electrical stimulation or during unilateral thermal stimulation of abdominal skin. Unilateral POAH warming produced vasodilation on both sides of the body, but vasodilation on the ipsilateral side always either occurred at a lower threshold hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Current evidence suggests that NO in the central nervous system is important in the thermoregulatory pathways mediating heat dissipation (13-15, 17, 54, 56). For example, thermal stimulation induces enhanced secretion of saliva, which is spread on the fur as a means of heat defense in rats (11,24). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that NO in the central nervous system is important in the thermoregulatory pathways mediating heat dissipation (13-15, 17, 54, 56). For example, thermal stimulation induces enhanced secretion of saliva, which is spread on the fur as a means of heat defense in rats (11,24). …”
mentioning
confidence: 99%
“…The latter autonomic cardiovascular responses often involve changes in sympathetic nerve activity (SNA) and result in the redistribution of blood flow from the viscera to the skin. These changes are mediated by the central nervous system (CNS) (24,25,40,43,45,52,65).…”
mentioning
confidence: 99%
“…The preoptic area in particular functions to monitor local temperature changes. Shivering is elicited when this area is cooled, and it is suppressed when it is warmed [3,4]. Our previous study has indicated that most efferent signals mediating these responses originate in warm-sensitive neurons [1, 2] and descend in the medial forebrain bundle [5].…”
mentioning
confidence: 99%
“…In the rat, as in all other species studied, the preoptic area contains neurones directly sensitive to changes in core temperature as well as neurones receiving inputs from peripheral thermoreceptors (Hellon & Taylor, 1982;Ishikawa et al 1984). Lesions in the preoptic area in the rat severely impair or abolish the ability to increase heat loss (Lipton, 1968(Lipton, , 1974Toth, 1973;Ishikawa et al 1984) and localised warming in the preoptic area of the rat at normal body temperatures activates the full range of heat loss behaviour (Lipton, 1973;Roberts & Martin, 1974;Ishikawa et al 1984;Nakayama et al 1986;Tanaka et al 1986;Kanosue et al 1990Kanosue et al , 1991. Neurones in the preoptic area of the rat also project to a wide range of midbrain and brainstem nuclei involved in autonomic functions, including those involved in the generation and control of breathing (Conrad & Pfaff, 1975, 1976Swanson, 1976;Veening et al 1982;Simerly & A. G. Boden, M. C. Harris and M. J. Parkes Exp.…”
Section: Hypothalamus and Thermoregulationmentioning
confidence: 99%